American Horticultural Society pruning and training - Brickell, Christopher (DK Pub., 1996)
Offers the information gardeners need to maintain attractive, well-pruned, and trained trees, shrubs, climbers, roses, and fruit. Includes a map of hardiness zones. Lots of detail.